Sustainable use of Baltic Sea resources. (27th September 2018) - Ojaveer, Henn; Neuenfeldt, Stefan; Dierking, Jan; Eek, Liina; Haldin, Jannica; Martin, Georg; Märtin, Kaire; Peterson, Kaja; Valanko, Sebastian
Abstract: The BONUS symposium "Science delivery for sustainable use of the Baltic Sea living resources" held in Tallinn, Estonia, in October 2017 was an opportunity for the presentation and discussion of 107 papers that examined the state and dynamics of living resources of the Baltic Sea, and associated management challenges. The symposium included a half-day stakeholder panel discussion that addressed the main challenges related to sustainable management and matching research and policy/management needs. Based on the five symposium papers published in this Special Issue as well as the stakeholder panel discussion, it can be concluded that (i) new observations about the feeding ecology of clupeids supports a more complete understanding of trophic interactions in the pelagic realm and improved calibration of ecosystem models, (ii) to safequard sustainable and diverse fisheries resources, one should take into account the specific local characteristics of the fish community, (iii) to safeguard sustainable use of marine resources and mitigate cross-sectoral and transboundary conflicts, a risk-based approach should be adopted, and (iv) incorporation of scientific advice into management faces several obstacles including the reality that not all readily available knowledge is currently being incorporated into the decision-making process.